1996
DOI: 10.1007/s002640050089
|View full text |Cite
|
Sign up to set email alerts
|

Primary osteoarthritis of the pisotriquetral joint

Abstract: We present a case of primary osteoarthritis of the pisotriquetral joint in a women aged 54 years. Radiographs in half-supination showed the joint with advanced degenerative changes. Excision of the pisiform confirmed the diagnosis and relieved the pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…5 The exact prevalence of PT OA is unclear, although over 200 individual cases have been reported in the literature. [6][7][8][9][10][11][12][13][14] A previous cadaveric study examined the prevalence of exposed subchondral bone of the pisiform and triquetrum separately and simultaneously, and reported cartilage lesions on either joint surface in 75.0% of cases. 15 A separate cadaveric study using MRI and MR arthrography reported cartilage lesions on the triquetrum and pisiform in 73 and 91% of cadaveric wrists, respectively.…”
mentioning
confidence: 99%
“…5 The exact prevalence of PT OA is unclear, although over 200 individual cases have been reported in the literature. [6][7][8][9][10][11][12][13][14] A previous cadaveric study examined the prevalence of exposed subchondral bone of the pisiform and triquetrum separately and simultaneously, and reported cartilage lesions on either joint surface in 75.0% of cases. 15 A separate cadaveric study using MRI and MR arthrography reported cartilage lesions on the triquetrum and pisiform in 73 and 91% of cadaveric wrists, respectively.…”
mentioning
confidence: 99%
“…Osteoarthritis of this joint is common, and when symptoms fail to resolve with nonoperative treatment including rest, splinting, and corticosteroid injection, excision of the pisiform is an effective treatment without notable functional sequelae. [15][16][17][18][19][20] More recently, posttraumatic pisotriquetral arthritis after triquetral malunion 21 and osteochondral fracture of the triquetrum 22 have been reported. In addition, pisiform ligament complex syndrome, as described by Rayan,23 should also be included in the differential diagnosis of pisotriquetral pain.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended technique for imaging the pisotriquetral joint space is an oblique view with the forearm in 30 to 40°supination and with the thumb extended (Needoff and Frostick, 1994;Perez Aguilar et al, 1996;Saitoh et al, 1997). Several attempts with slight alterations in position are often required until a tangential view of the joint is achieved.…”
mentioning
confidence: 99%